Endonasal endoscopic transsphenoidal pituitary surgery: early experience and outcome in paediatric Cushing's disease. (19th July 2013) - Storr, Helen L.; Drake, William M.; Evanson, Jane; Matson, Matthew; Berney, Dan M.; Grossman, Ashley B.; Akker, Scott A.; Monson, John P.; Alusi, Ghassan; Savage, Martin O.; Sabin, Ian
Summary Background Selective adenomectomy remains the first‐line treatment for Cushing's disease (CD), until recently by microscopic transsphenoidal pituitary surgery. Endonasal transsphenoidal endoscopic surgery (ETES) is emerging as a novel, less invasive treatment for pituitary adenomas and has become the optimal surgical approach. Objective There are no published series for the treatment of paediatric CD by ETES, and we report our centre's preliminary results. Design Retrospective analysis. Patients Six paediatric patients (median age 15·8 years; range 11·7–17·0 years) fulfilled standard diagnostic criteria for CD. Preoperatively, no abnormality was identified on pituitary MR scanning in 3 (50%) patients, one had a macroadenoma. Bilateral petrosal sinus sampling demonstrated central ACTH secretion (IPS/P ACTH ratio ≥3·0, post‐CRH) in 3/6 (50%) patients. The same neurosurgeon and endoscopic nasal surgeon undertook all the operations. Outcome measures Therapeutic outcome and rate of complications. Results Clinical recovery and biochemical 'cure' were achieved in 5 (83%) patients, and a corticotroph adenoma was confirmed histologically in all cured cases. One case developed post‐operative CSF leak requiring lumbar drain insertion and patching. At a mean interval of 4·7 years (0·1–10·8 years) post‐operatively, cured patients have shown no recurrence. One patient, with a large diffuse adenoma requiring more extensive surgery, has panhypopituitarism, and another patient has GH and gonadotrophin deficiencies. Conclusions Our experience shows that ETES for removing corticotroph adenomas in children, in most cases not visualized on MRI, is minimally invasive and gave excellent post‐operative recovery/results. In skilled hands, this technique provides an alternative to conventional transsphenoidal microscopic surgery in managing paediatric CD.